Cognitive profile in mild cognitive impairment with Lewy bodies - Shuai Liu; Chunyan Liu; Xiao-Dan Wang; Huiru Lu; Yong Ji (Singapore Medical Journal, 2023)
Introduction: This study aimed to elucidate the cognitive profile of patients with mild cognitive impairment with Lewy bodies (MCI-LB) and to compare it to that of patients with mild cognitive impairment due to Alzheimer’s disease (MCI-AD). Methods: Subjects older than 60 years with probable MCI-LB (n = 60) or MCI-AD (n = 60) were recruited. All patients were tested with Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) to assess their global cognitive profile. Results: The MCI-AD and MCI-LB patients did not differ in total MMSE and MoCA scores. However, some sub-items in MMSE and MoCA were shown to be screening markers for differentiating MCI-LB from MCI-AD. In the visuoconstructive test, the total score and hands subitem score in the clock-drawing test were significantly lower in MCI-LB than in MCI-AD. As for the executive function, the ‘animal fluency test’, ‘repeat digits backward test’ and ‘take paper by your right hand’ in MMSE all showed lower scores in MCI-LB compared with MCI-AD. As for memory, ‘velvet’ and ‘church’ in MoCA and ‘ball’ and ‘national flag’ in MMSE had lower scores in MCI-AD than in MCI-LB. Conclusion: This study presents the cognitive profile of patients with MCI-LB. In line with the literature on Dementia with Lewy bodies, our results showed lower performance on tests for visuoconstructive and executive function, whereas memory remained relatively spared in the early period.